(untitled) (Research, Society and Development, 2023)
This article aims to describe an experience report on an extension project on good health practices in primary care in a community linked to a UBS (Basic Health Unit) in the city of Fortaleza, Ceará. The work was divided into 3 stages, the first being to know the Frei Tito Primary Care Unit and identify the vulnerability points of the population. After that, there was the definition of the project that aimed to intervene in the food context of patients in the region and avoid diseases such as diabetes and hypertension, highlighting the presence of a CEADH (Specialized Center for Diabetics and Hypertensives), which weighed heavily for the choice from work. In the third and last step, the group was divided into 4 other subgroups that were responsible for printing educational “folders”, for digital “marketing”, for making the blood vessel in “biscuit” and for distributing coconut water. It is worth mentioning that the work was carried out with people of all ages, including pregnant women. It was concluded that University Extension projects constitute opportunities of multiple benefits, both for academics and professors, as well as for the participating community. The support offered by the University is extremely important, which should also be recognized by society because of the help offered.